Effect of maternal weight gain during pregnancy and gestational hypertension on birth weight of the baby - P., Chandrakala; Kumar N., Mohan; Patil, Vinutha; Nisha, Rahamuth (International Journal of Contemporary Pediatrics, 2022)
Background: Birth weight is not only an indicator of child growth and development but also valuable indicator of maternal health, nutrition and quality of life. Many maternal factors have been postulated to determine the birth weight of the baby like maternal age, weight, height, education, parity, antenatal care, maternal habits like smoking, sex of the baby and maternal comorbidities like hypertension. Methods: This study was conducted in Kempegowda institute of medical sciences Bangalore during the period of December 2019 to June 2021.All babies born with weight <2.5 kg weight were included in the study irrespective of gestational age. Mothers were divided into 3 categories based on weight gained during pregnancy into less than 10 kg, 10 to 15 kg and more than 15 kg weight gain. Low birth weight babies included in the study were categorized based on weight gain of the mother and presence of various maternal comorbidities like hypertension, diabetes, anemia, hypothyroidism. Results: Analysis showed that among 150 low birth weight babies 110 babies were born to mothers with weight gain less than 10 kg (73.3%), 37 (24.7%) babies were born to mothers with weight gain 10-15 kg and 3 (2%) babies were born to mothers with weight gain more than 15 kg. We also found that among all mothers of low-birth-weight babies 33.7% mothers did not have any comorbidities and gestational hypertension was found in 20.7% of mothers showing it as important risk factor for low-birth-weight babies. Conclusions: Our study shows adequate maternal weight gain during pregnancy independently influences birth weight of the baby. Thus, mother’s nutritional care should be appropriate to maintain adequate weight gain. Among all maternal comorbidities gestational hypertension is a major risk factor for low-birth-weight babies.